ZigBee wireless communication for monitoring renewable street light system - Ramachandran, T. (Institute of Electrical and Electronics Engineers Inc., 2014)
The advancement of technology brings advantages to human race to certain extent. Unfortunately, some of the technological inventions not only brings advantages, but also disadvantages. One of the disadvantages is the pollution of environment. Therefore, to prevent the pollution from getting worse, environmental-friendly aspect is suggested to be included in new inventions nowadays. Thanks to the invention of solar panel, solar energy is able to become a renewable energy source that can be applied to various applications. Considering the increase of electricity consumption every year in Malaysia, solar powered street lighting system is proposed in order to reduce the burning of fossil fuels to generate electricity, hence reducing air pollution. The street lighting system will consist of automated switching mechanism to further reduce the electricity consumption of street lights. The system will also be able to provide energy measurement to determine the efficiency of street lights. Some security features provided by selected wireless communication protocol will also be implemented to secure the system. Â© 2014 IEEE.